Optimization of Cutting Speed and Feed Rate on Surface Roughness and Vibration using Taguchi Method: A Review - Ilham, Mohammad; Suparjon, Suparjon; Sanjiwani, Yudistira (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
The result of a turning process is strongly influenced by the process parameters that could result in the product to be unacceptable. The cutting parameters may be determined according to the material hardness and roughness of the workpiece surface. The purpose of this paper is to investigate the effects of cutting speed and feed rate on surface roughness and vibration. In Taguchi method, the number of experiments is reduced by orthogonal arrays whileÂ the effects of uncontrollable factors are also also reduced. The Taguchi method is used to reduce track, experimental time and production cost. Simple and precise are the most benefits of this method. Unstable vibrations in machining operations, known as chats, can cause damage to tools, workpieces, and machine tools. Cutting force is found to be the most dominant factor affecting surface roughness.